2018
DOI: 10.1142/s0129065717500137
|View full text |Cite
|
Sign up to set email alerts
|

From Structure to Activity: Using Centrality Measures to Predict Neuronal Activity

Abstract: It is clear that the topological structure of a neural network somehow determines the activity of the neurons within it. In the present work, we ask to what extent it is possible to examine the structural features of a network and learn something about its activity? Specifically, we consider how the centrality (the importance of a node in a network) of a neuron correlates with its firing rate. To investigate, we apply an array of centrality measures, including In-Degree, Closeness, Betweenness, Eigenvector, Ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 65 publications
0
41
0
1
Order By: Relevance
“…Our definition of flow hierarchy was inspired by (Mones et al, 2012;Czégel and Palla, 2015), but based on modified (weighted) Katz centrality (Katz, 1953;Fletcher and Wennekers, 2018). To calculate Katz centrality, we assumed that each node j collected flows of incoming signals through all edges w ji leading to this node.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our definition of flow hierarchy was inspired by (Mones et al, 2012;Czégel and Palla, 2015), but based on modified (weighted) Katz centrality (Katz, 1953;Fletcher and Wennekers, 2018). To calculate Katz centrality, we assumed that each node j collected flows of incoming signals through all edges w ji leading to this node.…”
Section: Discussionmentioning
confidence: 99%
“…Flow hierarchy is a measure of structural hierarchy in the network (Mones et al, 2012), assessed through flows of activation that propagate through it. We based our measure of hierarchy on the distribution of Katz centrality values (Katz 1953;Fletcher and Wennekers 2018; see next section for definitions). Intuitively, hierarchy is high when a network has groups of "input" and "output" nodes, with connections between them largely pointing in the same direction, as it happens in layered feed-forward networks; hierarchy is weak in random networks, or networks that consist of cycles with no clear inputs and outputs (Czégel and Palla, 2015).…”
Section: Network Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The intended purpose of 48 such ranking was to filter the web pages and return the most relevant ones in response to a 49 query given to the search engine. However, the algorithm itself is universal and can usefully 50 be applied to other situations where one seeks to identify the importance of entities in a 51 networked system (for example, citation networks (Bollen et al, 2007;Ma et al, 2008), 52 biological networks (Banky et al, 2013;Fletcher and Wennekers, 2017; Ivan and Grolmusz, 53 2011), human movement (Gleich, 2015;Jiang et al, 2008), linguistics (Esuli and Sebastiani, 54 2007), or even networks of graduates' education institutes and employers (Schmidt and 55 Chingos, 2007)). Jiang (2009), in particular, has shown that there is a strong correlation 56 between the topological structure of human movement and PageRank scores in modern street 57 patterns.…”
mentioning
confidence: 99%